Unconventional Blooms: The Influence of the Craft Scotland Programme of Opportunities on the Development of Craft Practitioner Entrepreneurial Identities - Baker, Lauren (University of Dundee, 2022)
There is strong evidence to suggest that craft practitioners find it difficult to seize their potential as micro businesses and sole traders (Nielsen et al., 2018). Despite much work at the intersection between craft and entrepreneurial practice (Pret and Cogan, 2018), research shows a gap exists between the needs of craft business and the support provided by national organisations (Fillis, 2004; Bouette and Magee, 2015). Despite craft practitioners’ reliance on a non-linear, project-based approach to their entrepreneurial development, a conventionally entrepreneurial perspective is regularly applied to understanding craft businesses. Through advocacy for limited models of craft business, many ‘unconventional’ (Guercini and Cova, 2018, p.36) models have been marginalised, or left underexplored in literature. This has significant implications for the diversity (Eikhof, 2017; Patel, 2020) and longevity (Luckman, 2018) of the sector. However, craft’s tendency for activism holds potential for ‘political, economic and social transformation’ (Jakob, 2013, p.131) with many calling for the sector to be utilised as a space for political debate and action (Smith, 2016). As gatekeepers to opportunity and development, how can a national organisation better recognise the potential in the unconventional aspects of craft enterprise? Through the investigation of a key national craft development organisation, this doctoral research project seeks to advance the debate about entrepreneurial craft activities in Scotland and harness a more unconventional understanding.

Using Craft Scotland as a case study, the craft development organisation is presented as a dynamic and shifting actor placed within a complex entrepreneurial ecosystem. The vital relationships Craft Scotland upholds between the craft sector, craft events, and craft practitioners are explored in order to understand its position of influence regarding the development of entrepreneurial craft identities in the sector. Of particular interest is the role of practitioner participation in craft development opportunity, hosted by a craft development organisation, in the development of individual entrepreneurial craft identities, and how craft practitioners utilise programmes of support when sustaining their creative business practice. By addressing these issues, the research aims to explore the role of craft development organisations in the entrepreneurial development of Scottish craft practitioners. Doing so offers valuable insights that can inform the future delivery of support to build, promote, and sustain the working lives of craft practitioners. Three contributions to knowledge are made, beginning with the role of Craft Scotland as a cultural story maker. The metaphor of the ‘Unconventional Bloom’ is created to describe the interaction between a craft development opportunity and a craft practitioner, which is extrapolated to explain the way craft practitioners integrate the programmes of craft development opportunity in to their existing activities. Finally, a spectrum of unconventional craft entrepreneurship is presented.